2022
DOI: 10.3389/fvets.2022.1024088
|View full text |Cite
|
Sign up to set email alerts
|

The optimal PEEP after alveolar recruitment maneuver assessed by electrical impedance tomography in healthy horses

Abstract: BackgroundElectrical impedance tomography (EIT) has been an essential tool for assessing pulmonary ventilation in several situations, such as the alveolar recruitment maneuver (ARM) in PEEP titration to maintain the lungs open after atelectasis reversion. In the same way as in humans and dogs, in horses, this tool has been widely used to assess pulmonary aeration undergoing anesthesia, mechanical ventilation, recruitment maneuver, standing horses, or specific procedures.ObjectivesThe present study aimed to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
3
0
1
Order By: Relevance
“…15 The use of PEEP is believed to reduce atelectotrauma, 15,28 and it has been shown in multiple equine studies to improve V/Q mismatching and oxygenation. [10][11][12][13][14]29 However, studies have shown deleterious effects of PEEP, including pulmonary damage and cardiovascular compromise, and the optimal PEEP setting is dependent on species, context, and concurrent pathophysiologic processes. 16,30 It can be particularly challenging in situations with inhomogeneous lung pathology, such as the horse in dorsal recumbency or in a patient with acute respiratory distress syndrome (ARDS), to titrate ventilatory strategy and minimize further lung pathology.…”
Section: Discussionmentioning
confidence: 99%
“…15 The use of PEEP is believed to reduce atelectotrauma, 15,28 and it has been shown in multiple equine studies to improve V/Q mismatching and oxygenation. [10][11][12][13][14]29 However, studies have shown deleterious effects of PEEP, including pulmonary damage and cardiovascular compromise, and the optimal PEEP setting is dependent on species, context, and concurrent pathophysiologic processes. 16,30 It can be particularly challenging in situations with inhomogeneous lung pathology, such as the horse in dorsal recumbency or in a patient with acute respiratory distress syndrome (ARDS), to titrate ventilatory strategy and minimize further lung pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the degree of alveolar collapse can be reduced by application of an alveolar recruitment manoeuvre (ARM) and continuous PEEP [16,27,28]. An alternative approach consists of an ARM provided by stepwise incremental and decremental peak inspiratory pressure (PIP) and PEEP, which has been found to be amongst the most effective methods to redistribute ventilation and improve oxygenation [29,30]. Additional strategies involve the use of continuous CPAP, which also proved effective in redistributing ventilation to the dependent lung regions, thereby decreasing ventilation/perfusion mismatch [23].…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] However, high values of PIP in patients with atelectasis have been associated with an increased risk of hypoxaemia, 5 presumably related to volutrauma 11 due to overexpansion of a reduced number of open alveoli. As the initial PIP in this case was already greater than 30 mmHg (>3.9 kPa), the first attempt to improve oxygenation and respiratory mechanics was conservative and consisted of an increase in T v and inspiratory time 22,[24][25][26] and by the addition of PEEP.…”
Section: Discussionmentioning
confidence: 99%